Context matters: Examining the factors impacting the implementation of tuberculosis infection prevention and control guidelines in health settings in seven high tuberculosis burden countries. Issue 5 (May 2021) - Islam, M. Saiful; Chughtai, Abrar Ahmad; Banu, Sayera; Seale, Holly
Highlights: Low-income high TB burden countries face significant challenges to the local adoption and implementation of international TB IPC guidelines. National TB IPC guidelines lacked examples and evidence from local context. Our study warrant involving frontline healthcare workers in the early phase of the guidelines development. Voices of frontline workers in the guidelines may enhance the acceptability, practicality, and implementation of TB IPC guidelines. Abstract: Background: Healthcare workers (HCWs) in high tuberculosis (TB) burden countries are at increased risk of TB infection due to increased exposures to TB patients and inadequate implementation of TB infection prevention and control (TB IPC) measures in health settings. While various guidelines on TB IPC exist, there is little understanding of the content of these guidelines, whether they are relevant to the context and are being appropriately implemented in low-and middle-income high TB burden countries. This study aimed to critically examine the implementation of TB IPC guidelines, along with factors impacting TB IPC implementation in health settings in seven high TB burden countries. Methods: The WHO 2009 and national level TB IPC guidelines and the published literature from seven TB high burden countries were reviewed and relevant information extracted. Eleven key-stakeholders from the case study countries were interviewed to elucidate further facilitators and barriers impacting TB IPC guidelines implementation. Results: Our study identified that all the study countries adopted the WHO 2009 guidelines with no or minimal modifications for the local context. Therefore, the subsequent translation of the TB IPC recommendations into practice has been limited and impaired in some settings. Poor infrastructure, inadequate space for isolation, lack of TB IPC training, limited supply of personal protective equipment, the discomfort of using N95 respirators, and a high number of TB patients were some of the factors impacting the implementation of TB IPC guidelines. Conclusion: The implementation of TB IPC guidelines in all seven countries was limited. It was affected by the diverse context where each of the countries and each of the facilities had a different health infrastructure and TB disease burdens. The findings warrant re-assessment of the current context prevailing in these high TB burden countries and subsequent revisions of national guidelines based to account for local context and evidence.